Evaluating the Accuracy of Smartphone Light Sensors in a Uniformly Accelerated Motion Experiment - Rahma Alliya Aqquilla; Najmi Hiyan Fathinah; Asep Akmal Fadia Nurhalim; Ika Mustika Sari; Alfiansah Sandion Prakoso; Rizki Zakwandi (Jurnal Teori dan Aplikasi Fisika, 2026)
This study aims to design and implement a motion experiment using a smartphone’s light sensor, powered by the Phyphox application, to investigate uniformly accelerated linear motion. A dynamic cart equipped with a smartphone was released along a rail inclined at 1°, with an LED strip serving as the light source. The smartphone's light sensor recorded variations in light intensity as the cart moved, allowing for the determination of acceleration over time. Data analysis focused on the relationship between acceleration and motion, demonstrating consistent acceleration values ranging from 0.127 m/s² to 0.128 m/s² across multiple trials. The LED setup was adjusted to optimize data collection, ensuring the reliability of measurements. These results confirm the theoretical principles of uniformly accelerated motion and highlight the effectiveness of smartphone-based sensors for experimental and educational applications. Despite a percentage error of approximately 25% when compared to theoretical calculations, the small standard deviation value of 0.000242 indicates a high level of precision and repeatability in the experimental results. This suggests that the experiment, although not perfectly accurate, can still serve as a reliable instructional tool in physics classrooms. The experimental design is not only low-cost and portable but also adaptable to different learning environments, making it a suitable alternative when conventional lab tools are unavailable. Future research could explore alternative sensor configurations or extended applications in physics education. Additionally, improvements in the light sensor’s sensitivity, optimizing the distance between light sources, and using more mobile supporting structures are recommended to increase data accuracy and ease of implementation in physics experiments for students studying linear motion.     Keywords: inclined plane; light sensor; linear motion; lux meter; phyphox.